Benefits of heart failure-specific pharmacotherapy in frail hospitalised patients: a cross-sectional study. Issue 9 (19th September 2022) - Sharma, Yogesh; Horwood, Chris; Hakendorf, Paul; Thompson, Campbell
Abstract : Objectives: Up to 50% of heart failure (HF) patients may be frail and have worse clinical outcomes than non-frail patients. The benefits of HF-specific pharmacotherapy (beta-blockers, ACE-inhibitors/angiotensin-receptor-blockers and mineralocorticoid-receptor-antagonist) in this population are unclear. This study explored whether HF-specific pharmacotherapy improves outcomes in frail hospitalised HF patients. Design: Observational, multicentre, cross-sectional study. Settings: Tertiary care hospitals. Participants: One thousand four hundred and six hospitalised frail HF patients admitted between 1 January 2013 and 31 December 2020. Measures: The Hospital Frailty Risk Score (HFRS) determined frailty status and patients with HFRS ≥5 were classified as frail. The primary outcomes included the days alive and out of hospital (DAOH) at 90 days following discharge, 30-day and 180-day mortality, length of hospital stay (LOS) and 30-day readmissions. Propensity score matching (PSM) compared clinical outcomes depending on the receipt of HF-specific pharmacotherapy. Results: Of 5734 HF patients admitted over a period of 8 years, 1406 (24.5%) were identified as frail according to the HFRS and were included in this study. Of 1406 frail HF patients, 1025 (72.9%) received HF-specific pharmacotherapy compared with 381 (27.1%) who did not receive any of these medications. Frail HF patients who did not receive HF-specific pharmacotherapy were significantly older, with higher creatinine and brain natriuretic peptide but with lower haemoglobin and albumin levels (p<0.05) when compared with those frail patients who received HF medications. After PSM frail patients on treatment were more likely to have an increased DAOH (coefficient 16.18, 95% CI 6.32 to 26.04, p=0.001) than those who were not on treatment. Both 30-day (OR 0.30, 95% CI 0.23 to 0.39, p<0.001) and 180-day mortality (OR 0.43, 95% CI 0.33 to 0.54, p<0.001) were significantly lower in frail patients on HF treatment but, there were no significant differences in LOS and 30-day readmissions (p>0.05). Conclusion: This study found an association between the use of HF-specific pharmacotherapy and improved clinical outcomes in frail HF hospitalised patients when compared to those who were not on treatment. Trial registration number: ANZCTRN383195.